The Fish-Specific Protein Kinase (PKZ) Initiates Innate Immune Responses via IRF3- and ISGF3-Like Mediated Pathways - Xu, Xiaowen; Li, Meifeng; Wu, Chuxin; Li, Dongming; Jiang, Zeyin; Liu, Changxin; Cheng, Bo; Mao, Huiling; Hu, Chengyu (Frontiers in Immunology, 2019)
Protein kinase containing Zα domain (PKZ) is a fish specific protein kinase. PKZ can induce apoptosis through phosphorylating eIF2α, which is similar to PKR. However, its unique roles in recognition of pathogen remain to be fully elucidated. Herein, we identify PKZ acts as a fish special DNA sensor which can initiate IFN expression through IRF3- or ISGF3-like-mediated pathway. Firstly, the expression pattern of PKZ is similar to those of innate immune mediators under stimulation with poly (dA:dT) and poly (dG:dC). As a DNA sensor, PKZ can interact with DNA but not with ISD-PS (dsRNA analog), and expectedly, the DNA-PKZ interaction promotes the phosphorylation and dimerization of PKZ in vitro. These indicate that PKZ participates in cytoplasmic DNA-mediated signaling pathway. Besides, subcellular localization assays showed that PKZ is located in the cytoplasm, which suggests that PKZ acts as a cytoplasmic PRR. In addition, co-IP assays showed that PKZ can separately interact with IRF3, STING, ZDHHC1, eIF2α, IRF9 and STAT2. Further investigation revealed that PKZ can activate IRF3 and STAT2. Moreover, IRF3-dependent and ISGF3-like-dependent mediators are critical for PKZ initiated IFN expression. In a word, these results demonstrated that PKZ acts as a special DNA pattern-recognition receptor, and PKZ can initiate innate immune responses through IRF3-mediated or ISGF3-like mediated pathways in fish.